Sử dụng hệ cappa cho việc xây dựng kế hoạch phát triển nông nghiệp Việt Nam - Lập, Hoàng Trung (Journal of Computer Science and Cybernetics, 2016)
The purpose of this paper is to show an application of the system CAPPA to agricultural development in Vietnam.